HISTEROCELE INGUINAL COM ENCARCERAMENTO FETAL EM UMA FÊMEA CANINA - Barella, Paola Andressa Das Chagas; Chitolina, Thalia; Bender, Carla Gabriela; Rick, Gabriel Woermann; Junior, Antônio Maieron (Salão do Conhecimento, 2019)
Relatório de caso clínico cirúrgico